Management issues of professionals’ background within the framework of the MA courses - Lunyachek, V. (Problems of Engineer-Pedagogical Education, 2018)
The paper provides insight into the issue of professional training in terms of Master’s degree program, which can be solved by the adoption of certain management decisions without significant additional resources.It is referred to creation and functioning of structures within institutions in higher education, which should work to improve quality of higher education, as well as qualification of the teaching staff to implement the competence approach in terms of Master’s degree program, ensuring academic integrity by implementing a process approach at all stages of education, etc. Special attention is paid to the problem of harmonization of curricula of bachelor's, master's and PhD programs to avoid duplication of learning material. Discusses the involvement of students to scientific work with a focus on further education in graduate school. Proposed start practice grants and preferential loans from employers for students of contract form of training and other means of motivation and stimulation